2014
DOI: 10.1017/s1049023x14001356
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Cardiovascular Morbidity and Mortality Following Humanitarian Emergencies: A Systematic Literature Review

Abstract: Background The global burden of cardiovascular mortality is increasing, as is the number of large-scale humanitarian emergencies. The interaction between these phenomena is not well understood. This review aims to clarify the relationship between humanitarian emergencies and cardiovascular morbidity and mortality. Methods With assistance from a research librarian, electronic databases (PubMed, Scopus, CINAHL, Global Health) were searched in January 2014. Findings were supplemented by reviewing citations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 35 publications
(159 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, another study on Hurricane Sandy also demonstrated that diabetic adults aged 65 years and older were especially at risk for developing acute myocardial infarction the week after that extreme weather event48. The development of ACS in the above-mentioned studies was attributed to the psychological stress of the event and corresponding physiologic derangements49. Although we agree that acute psychological stress plays a role in triggering cardiac events, our results show that other factors are also involved.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, another study on Hurricane Sandy also demonstrated that diabetic adults aged 65 years and older were especially at risk for developing acute myocardial infarction the week after that extreme weather event48. The development of ACS in the above-mentioned studies was attributed to the psychological stress of the event and corresponding physiologic derangements49. Although we agree that acute psychological stress plays a role in triggering cardiac events, our results show that other factors are also involved.…”
Section: Discussionsupporting
confidence: 49%
“…The top 25 global EM articles for 2014 are listed in Table . The complete database of all 477 global EM articles for 2014, as well as full summaries and critical analyses of the top 25 global EM articles of 2014 can be found in Data Supplements S1 and S2 (available as supporting information in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Hayman et al . performed a systematic review to evaluate the interaction between the increasing frequency of large‐scale humanitarian emergencies and global burden of cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…While there is growing evidence on the burden and gaps in access to care for NCDs in humanitarian crisis settings, very little has been published on the cost effective management of NCDs in general, and still less on the management of ASCVD, in humanitarian settings [11][12][13][14][15]. This is a significant gap, especially given that limited evidence shows that crises may actually increase CVD mortality, morbidity and risk factors [12,[16][17][18]. Commentators have noted the challenges that exist around identifying and treating ASCVD even in high-income, stable settings with ready access to medications and diagnostics [19].…”
Section: Introductionmentioning
confidence: 99%